Hubungan Tingkat Pengetahuan Remaja tentang Kesehatan Reproduksi dengan Perilaku Seks Bebas di SMK PGRI I Mejayan - Eny Pemilu Kusparlina (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Abortion rates in Indonesia are estimated at 2.3 million per year, around 750,000 of them are carried out by teenagers. The results of the study on the sexual behavior of adolescents in ten public and private high schools in Madiun District in 2012 of 1,250 people (611 male subjects and 639 female subjects) found that 30% of men dating had had sexual relations, while for women as much as 5%. It can be said that every 3 boys are dating, one of them has had sexual relations and they on average start doing it in second and third grade. From the preliminary study conducted, The researcher obtained information from the student affairs department that in 2012-2018 there were 2 students pregnant and forced to be expelled from school. This study purpose to determine the relationship between adolescent knowledge about reproductive health and free sex behavior at SMK PGRI I Mejayan. This study used an observational analytic design with a cross sectional design. The sampling technique used was simple random sampling with a sample size of 68 students. Analyze the data using the Kendall Tau correlation test (τ). The results of the study were 48 students (70.6%) had good knowledge about reproductive health and 51 students (75.0%) had good behavior in the association of free sex. From the results of data analysis with Kendall Tau obtained Zcount (9,96)> Ztable (1,96). The conclusion of this study is that there is a significant relationship between adolescent knowledge about reproductive health with free sex.